Impact of vehicular tailpipe characteristics on roadside environmental quality - Mah, Kang Tai (2017)
Singapore adopts a right-hand-drive convention and drivers drive their cars on the left of the road. Certain problems arise when vehicles manufactured in the United States of America and Continental European countries are exported to Singapore. As these vehicles are designed for usage in their home grounds, their vehicular tailpipes are positioned on the left side of the vehicles, which is nearer to the roadside pedestrian paths in Singapore. Road users like pedestrians, motorcyclists and cyclists experience an increase in the amount of vehicular exhaust fumes from left-hand-drive vehicles due to the closer proximity to the tailpipe. Wherever possible, efforts should be made to reduce the amount of exposure to vehicular exhaust fumes given the underlying negative health impacts. Thus, it is paramount to study the impacts of the vehicular tailpipe characteristics on the environmental quality of the roads. The study focuses on the situation at the bus shelters as buses generate a substantial volume of diesel fuel exhaust fumes. More importantly, bus shelters are locations with higher densities of sedentary human traffic. The time taken for the commuters to board and alight from the buses equates to the idling time of the buses spent at the bus bay, thereby increasing the duration which commuters are exposed to the exhaust fumes. Also, as the buses move off from a stationary position, they must accelerate and the exhaust fumes emitted will increase. From the experimental data, the amount of vehicular exhaust fumes which commuters are exposed to is found to be inversely proportionate to the distance to the tailpipe. The position and the orientation of the tailpipe contribute to the amount of particulate matter and harmful gases which the commuters are exposed to, which is more observable on the ground level.